Organisational structure and external relations of an international road freight carrier (Economics and region, 2024)
The purpose of the study is to examine the organisational structure and external relations of an international road freight carrier, as well as the functions and tasks of its personnel. One of the domestic companies engaged in international road freight transportation was selected for the analysis. It has been determined that the company has a line-functional organisational management structure, where the line units make decisions and the functional units ensure their implementation. The organisational structure of the international road freight carrier has a peculiarity – it has two departments: logistics and forwarding and transport haulage. The assistant to the director, heads and managers of the company’s main departments have the most extensive list of performed functions and tasks. The main difference between the activities of the logistics department and the forwarding and transport haulage department is that the former provides transport services with the using the company’s own vehicles, while the latter engages other carriers for transportation. The external organisations with which the international road freight carrier contacts can be divided into several groups: counterparties, regulatory authorities, and the bank.
Keywords: international road freight carrier; organisational structure; management levels; functions and tasks of personnel; external relations